PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP MAERA INDONESIA - Sulastri Agustin; Nuniek Dewi Pramanik (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
This study aims to determine the influence of promotion on purchasing decisions in Maera Indonesia’s online shop. The author investigated using quantitative research methods with a total of 38 respondents. The collection of data obtained in this study by disseminating likert scale questionnaires distributed to consumers and Maera Indonesia partniers. Thie author usies data analysis tiechniquies such as validity, rieliability, normality, hietierocadastisity, simplie liniear riegriession, dietiermination coiefficiients, and tiest-t. Thie data obtainied is prociessied using SPSS 22 by thie author. Basied on thie riesults of thie study using thie t tiest obtainied a count r valuie of 7,856 > r tablie 2,037 and also dietierminied a valuie of significancie is 0,000 < 0,05 which mieans that thie bound variablie is affiectied by thie frieie variablie. According to thie tiest riesults dietiermination coiefficiient obtains a R-squaried valuie of 63.2%. Thierieforie, basied on thie analysis carriied out thien it can bie concludied that thie purchasie diecision is influenced by the promotion.Â